Tissue‐specific mosaicism in hereditary hemorrhagic telangiectasia: Implications for genetic testing in families. Issue 7 (7th May 2018) - McDonald, Jamie; Wooderchak‐Donahue, Whitney L.; Henderson, Katharine; Paul, Eleri; Morris, Ashley; Bayrak‐Toydemir, Pinar
Abstract : Mosaicism in hemorrhagic telangiectasia (HHT) has been previously identified when testing blood samples of HHT patients. We report the first detection of mosaicism not involving blood of a family proband, and discuss implications for genetic testing algorithms in HHT families. Sanger sequencing and large deletion/duplication analysis in a patient with HHT identified no pathogenic variant in ENG, ACVRL1, or SMAD4 . Exome sequencing was then performed on this proband, as well as her affected adult child. A pathogenic ENG variant was detected in the proband's affected child, but not in DNA extracted from peripheral blood of the affected parent/proband. Additional tissue samples (saliva and hair bulbs) were obtained from the proband. The variant was not detected in saliva, but was detected in the hair bulb sample (at 33%). This is the first report of an HHT patient with mosaicism in whom the disease‐causing mutation was not detected in blood. The molecular findings in this family suggest that the possibility of mosaicism not present or detectable in blood should be considered if a proband with HHT tests "negative" for a mutation in known genes. This occurrence is particularly suspect for families in which the proband does not have a clearly affected parent. This mechanism may explain some patients with classic HHT in whom a pathogenic variant has not been identified in one of the known HHT genes.